Heat Transfer with Specular Reflections in an Experimental Annealing Device. Issue 1 (2015) - Jadachowski, L.; Steinboeck, A.; Kugi, A.
Abstract: A first-principles distributed-parameter model of the temperature in an experimental annealing device is developed. In particular, the one-dimensional spatial-temporal temperature evolution of a thin steel strip along its length is modeled during the heating-up process assuming temperature uniformity along the width and the thickness. The model captures heat flows caused by thermal radiation in the considered partially specular enclosure, free convection, and in-domain convection. Parameter identification is carried out based on the step response of the system measured by thermocouples and an infrared camera. For model verification, both time and spatial evolutions of the simulated specimen temperature are compared with measurements.